Komitmen Organisasi Merupakan Variabel Mediasi Hubungan Kompensasi Finansial dan Kompensasi Non Finansial terhadap Kinerja Karyawan (Studi pada Karyawan PT Bank UOB Buana Capem Tabanan-Bali) - Bagyo, Yupono (Jurnal Aplikasi Manajemen, 2009)
Company activities obtained by involving human as a resource whose have capability to be developed. In accordance to those problems, this research intended to verify the correlations between financial compensation, non-financial compensation, organizational commitment, and employee performance. The chosen samples are 18 PT. UOB Buana Bank-Tabanan subsidiary employees by using stratified random sampling methods.Using Path analysis, this research found that financial compensation variable and non-financial compensation are simultaneously and significantly have correlations with employees performance; however non-financial compensation variable partially have not significantly correlated. Employee performance is directly affected by financial compensation variable and non-financial compensation variable, without passing through organization commitment variable. This finding is based on Path value that shows financial compensation variable and non-financial compensation directly toward employee performance are higher than Path value of financial compensation and non-financial compensation towards performance through organizational commitment variable. The employee performance is higher due to financial compensation and non financial compensation which have given by the company. The given compensations could make employees feels satisfied; nor because of the employees high commitment to their company.Keywords: Direct Effect, Indirect Effect, Financial Compensation, Non-Financial Compensation, Organizational Commitment, Employee Performance